Integração das tecnologias digitais de informação e comunicação em cursos de natureza agrotécnica por meio de metodologias ativas - Perrier, Gerlane Romão Fonseca (2019)
This thesis analyzes the dynamics/methodologies developed with the use of digital information and communication technologies (DICT) in pedagogical practice and the changes evidenced in the curriculum, in tune with the curricular changes occurred due to the Professional Education Reform. The research deals with the development of integrative practices of DICT with the use of active methodologies, aiming at favoring students’ participation and engagement, through a qualitative research methodology developed in collaboration with teachers of courses of an agricultural nature. Action research was adopted, which included both the theoretical and documentary approach, as well as field research, based on ongoing curricular subjects of an agrarian nature. It was proposed and developed actions seeking to enhance teaching practices from the incorporation of DICT into teaching and learning processes, designed for the specific context of each discipline, that is, in accordance with the needs and possibilities of each group of teachers and their students. The data were analyzed by means of the content analysis technique, in the three phases of the methodological design: diagnosis, intervention and analysis. The exploitation of the material collected and produced occurred with the definition of categories and treatment of the results, through the Mendeley, NVivo 12 Pro for Windows and DSCsoft 2.0 softwares, according to the nature of the data; inference and interpretation. The results point out the potential of the active methodologies for theory and practice articulation in courses of a technical nature, as well as they confirm the potentiality of using digital narratives and games to promote a collaborative learning environment, as well as the possibility of extrapolating this experience to other disciplines and courses